Implementing Yogyakarta Pediatric Cancer Registry for 16 years - Sri Mulatsih; Adnina Hariningrum; Ignatius Purwanto; Rizki Oktasari (Indonesian Pediatric Society, 2019)
Background A hospital-based cancer registry can be used as a guide to decision-making. Considering the limited cancer registry data in the population, the Yogyakarta Pediatric Cancer Registry (YPCR) is one of the pioneers of hospital-based pediatric cancer registries in Indonesia. The YPCR was started in 2000 in Dr. Sardjito Hospital. Objective To describe the characteristics of childhood cancer and the outcomes by analyzing overall survival (OS) and event-free survival (EFS) based on data from Yogyakarta Pediatric Cancer Registry. Methods Data were collected from the YPCR for the period of 2000 to 2016. Childhood cancers were classified into 12 groups based on the 3rd edition International Classification for Childhood Cancer (ICCC). Incidence, frequency, and distribution of cases were grouped by sex, age, and patients’ place of residence. Incidence was further analyzed using SPSS software. Kaplan-Meier test was used to analyze OS and EFS. Results Within the study period, 2,441 children aged 0-18 years were diagnosed with cancer. The highest incidence was found in the 1-5-year age group. The most common diagnoses found were leukemia, myeloproliferative disorders, and myelodysplastic disease (58%); lymphoma and reticuloendothelial neoplasm (8%); retinoblastoma (6%); soft tissue and other extra-osseous sarcomas (5%); as well as neuroblastoma and other peripheral nervous cell tumors (5%). The OSs of acute lymphoblastic leukemia (ALL), high risk ALL (HR-ALL), and standard risk (SR-ALL) were 31.8%, 18.5%, and 43.9%, respectively. The EFSs of ALL, HR-ALL, and SR-ALL were 23.9%, 14.7%, and 32.4%, respectively. For solid tumors, the OS was 13.7% and EFS was 6.4%. Conclusion The number of new cases of childhood cancer has increased in the last few years. The Yogyakarta Pediatric Cancer Registry (YPCR), which serves as a hospital-based pediatric cancer registry, has an important role to evaluate clinical and non-clinical aspects of childhood cancer.